Adolescents’ self-reported health status, behaviours and health issues addressed during routine school doctor consultations in Switzerland: an observational study - Yael Rachamin; Sofia Elena Nerlich; Levy Jäger; Saskia Maria De Gani; Olivier Favre; Oliver Senn (Swiss Medical Weekly)
BACKGROUND: We aimed to investigate the self-reported health status and behaviours of 7th-grade adolescents, associations with gender and educational track, as well as health issues addressed during routine school doctor consultations in Switzerland.